THE RELATIONSHIP OF PRODUCT KNOWLEDGE, COMPANY IMAGE, AND PROMOTION ON PURCHASING DECISIONS FOR UNILEVER INDONESIA PRODUCTS IN SIDOARJO - Rangga Ramadhani; Rizky Eka Febriansah (Journal of Artificial Intelligence and Digital Economy, 2024)
Objective: This study aims to examine the relationship between product knowledge, company image, and promotional activities with consumer purchasing decisions in the context of an increasingly competitive business environment. Method: A quantitative research design with a correlational approach was employed, involving a sample of 100 respondents selected to represent consumer perceptions. Data were analyzed statistically to determine the strength and significance of relationships among the studied variables. Results: The findings reveal that product knowledge, company image, and promotion each have a positive and significant relationship with purchasing decisions. These results indicate that consumers’ understanding of products, perceptions of corporate reputation, and exposure to promotional efforts jointly influence their decision-making process. Novelty: This research contributes to the existing literature by providing updated empirical evidence on the determinants of purchasing behavior in Indonesia, highlighting the synergistic role of cognitive and perceptual factors in shaping consumer decisions within an emerging market context.